2021
DOI: 10.1097/iyc.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perspectives on Strength-Based and Deficit-Based Instruments for Assessing Socioemotional Development in Early Childhood

Abstract: This study compares teachers' perspectives on three assessment instruments for socioemotional development in early childhood, which differ in their emphasis on strengths and difficulties in this domain: the Caregiver-Teacher Report Form (C-TRF), the Strengths and Difficulties Questionnaire, Teacher version (SDQ-T), and the Social Emotional Assessment Measure (SEAM). We examine the teachers' views on the clarity, relevance, and acceptability, as well as estimating average completion times, of the three question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our study found strong correlations between play observations and social-emotional competences in educator rating, suggesting effective measurement of social-emotional development in young refugee children. Notably, no corresponding correlations emerged with general symptom scores, suggesting that strength-based measures and our play observations may more accurately assess children's psychosocial competences than deficit-focused measures [15,44]. Solely assessing children's symptom load may underestimate children's abilities, as social-emotional competences in a specific context may not equate to the absence of problembased behavior [44].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our study found strong correlations between play observations and social-emotional competences in educator rating, suggesting effective measurement of social-emotional development in young refugee children. Notably, no corresponding correlations emerged with general symptom scores, suggesting that strength-based measures and our play observations may more accurately assess children's psychosocial competences than deficit-focused measures [15,44]. Solely assessing children's symptom load may underestimate children's abilities, as social-emotional competences in a specific context may not equate to the absence of problembased behavior [44].…”
Section: Discussionmentioning
confidence: 72%
“…Notably, no corresponding correlations emerged with general symptom scores, suggesting that strength-based measures and our play observations may more accurately assess children's psychosocial competences than deficit-focused measures [15,44]. Solely assessing children's symptom load may underestimate children's abilities, as social-emotional competences in a specific context may not equate to the absence of problembased behavior [44]. Our findings highlight both difficulties and social-emotional abilities of refugee children, setting a focus on their resilience in the face of refugee accommodations in which the educator reports where obtained [34].…”
Section: Discussionmentioning
confidence: 76%
“…For this reason, its content could also be useful for suggesting strategies aimed at strengthening social competence and play between children. Strength-based formulations had higher acceptability among Danish teachers than deficit-based instruments, in a recent comparison (Sjö et al, 2021). The reception of the teachers and their willingness to use the observation instrument TIS may be related to its strength-based characteristics.…”
Section: Discussionmentioning
confidence: 96%
“…This combination is particularly beneficial in identifying potential mental health or developmental problems, addressing some limitations of the ASQ. Both SEAM and SDQ utilize a strength-based approach, focusing on various aspects of child development (Du et al, 2008; Goodman, 2001; Sjö et al, 2021).…”
Section: Social-emotional Assessment Measurementioning
confidence: 99%